An analysis of media text on "Integrated Korean Team": The revolving stage of politics and sports - Suyong Oh; Bang-Chool Kim (Korea Institute of Sport Science, 2020)
The purpose of this study was to critically interpret a certain sports-related idea, "Integrated Korean Team," which was an issue at the PyeongChang Winter Olympics. The idea emerges as a specific political agenda under the conditions of domestic politics and the special environment of Korean national affairs and discourse. To this end, we investigated media texts on the relationship between sports, political dynamics and views on related discourse that were produced in 1990-1991 and 2018. The main findings are as follows: First, sports functions as a political socialization tool for political power as it forms public opinion. Second, sports exchanges work as a kind of international politics. Specifically, political power controls sports as certain political situations arise and political elites' needs change. Third, mega sports events have tended to become politicized in recent years as they become more effective. Fourth, North Korea's sports under political power cannot be easily dealt with by the private sector, and it has limitations because it is not politically independent. The analysis showed that the negotiation process and realization of the Integrated North and South Korean Team seemed to be a turning point in politics and sports. Here are the conclusions drawn from discussing the two unifying events in 1991 and the situation in 2018. First, both South and North Korea pulled the Integrated Korean Team card when political needs arose. Second, when the two Koreas did not need to reconcile due to changes in the political situation between the two Koreas, they did not want to make efforts to integrate Korean Team. Third, the position of the political elite was directly represented by the position of the South-North Korean team. Fourth, the supporting public opinions of the Integrated Korean Team are gradually diminishing as the power gap between the two Koreas widens and sports players' human rights issues emerge.